When the team's jersey is what matters: Network analysis of party cohesion and structure in the Canadian House of Commons. (September 2020) - Chartash, David; Caruana, Nicholas J; Dickinson, Markus; Stephenson, Laura B
Are parties "high discipline, low cohesion" in Westminster legislatures? This study applies network analysis to voting behavior among members of parliament (MPs), a novel approach that measures not deviation from party-line voting, but rather whether MPs with similar voting patterns are co-partisans. We study the Canadian Parliament from 2006 to 2015, during which time the governing party under Prime Minister Stephen Harper maintained tight central control and discipline, a likely source of elevated cohesion. We find that "low cohesion" generally holds, and parties do not always conform to commonsense expectations about how cohesively they "should" behave in various parliamentary situations, though they show themselves capable of learning over time. Moreover, we find that party cohesion stems less from shared voting behaviors and more from simple partisan identity. Further research should consider to what extent parliamentary behavior is based mainly on party alignment.